2019
DOI: 10.1029/2018wr023316
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Rainfall in Colombia

Abstract: The knowledge of the annual cycle of rainfall is of primary concern for many socioeconomic activities such as agricultural planning, electricity generation, and flood and other disaster management. The annual cycle of rainfall in Colombia has been studied so far using monthly or quarterly information, identifying zones with the unimodal regime (one wet season and one dry season) over the Caribbean, the Amazon, and the Pacific regions and zones with the bimodal regime (two wet and two dry seasons) in the Andes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 33 publications
9
55
0
3
Order By: Relevance
“…We primarily use precipitation from the widely-used high-resolution (0.25°× 0.25°) Climate Hazards group Infrared Precipitation with Stations (CHIRPS version 2) dataset (1981 to present). The CHIRPS daily precipitation dataset has been used for the assessment of daily, monthly, seasonal, and annual precipitation characteristics in several regions of the world [65][66][67][68] . CHIRPS blends satellite-based precipitation estimates with in situ observations, and models of terrain-based precipitation modification to provide high resolution, spatially-complete, and continuous long-term data from 1981 to present, providing distinct advantages over rain-gauge-based products that include variations in station density or remotely sensed data that have a limited temporal extent 69,70 .…”
Section: Methods Datamentioning
confidence: 99%
“…We primarily use precipitation from the widely-used high-resolution (0.25°× 0.25°) Climate Hazards group Infrared Precipitation with Stations (CHIRPS version 2) dataset (1981 to present). The CHIRPS daily precipitation dataset has been used for the assessment of daily, monthly, seasonal, and annual precipitation characteristics in several regions of the world [65][66][67][68] . CHIRPS blends satellite-based precipitation estimates with in situ observations, and models of terrain-based precipitation modification to provide high resolution, spatially-complete, and continuous long-term data from 1981 to present, providing distinct advantages over rain-gauge-based products that include variations in station density or remotely sensed data that have a limited temporal extent 69,70 .…”
Section: Methods Datamentioning
confidence: 99%
“…Regarding when it rains, it is worth noting that 3B43 V7 is able to capture, equally precise, the phase of both the unimodal and bimodal annual cycles of mean precipitation at monthly resolution that coexist all over Colombia (Poveda et al, 2006;Urrea et al, 2019), not only on the pixels shown in Figure 3 but on the 427 validation pixels (not shown). This capability seems to be unaffected by the particularities of each region such as topography, climate, land cover and vegetation, among others.…”
Section: Metricmentioning
confidence: 97%
“…The high precipitation rates observed are a result of the orographic effects over the moisture coming from the Pacific Ocean (Guzmán et al, 2014;Poveda Jaramillo et al, 2014), which are then generated due to permanent convective activity in the region throughout the year (Zea et al, 2000), as well as the influence of the "CHOCO jet" presents larger magnitudes (Hoyos et al, 2018). This climatic and orographic effect combination is responsible Hydrological responses in equatorial watersheds indicated by Principal Components Analysis (PCA) -study case in Atrato River Basin (Colombia) for the existence of different types of hydrometeorological cycles, in regard to precipitation and to river discharge as well (Urrea et al, 2019).…”
Section: Study Areamentioning
confidence: 99%